2020
DOI: 10.1371/journal.pone.0242352
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of job loss among schizophrenia outpatients at St. AmanuelMental Specialized Hospital, Addis Ababa, Ethiopia; cross sectional study

Abstract: Background Job loss in patient with chronic illness like schizophrenia is the most serious public concern in the clinical and socio-economic terms worldwide. Patients with schizophrenia usually have unsatisfactory job termination like quitting or getting fired which results well-established negative outcomes. The complex interplay between one another has made job and mental illness the focus areas. In the developing nations, there is limited study on these areas in spite of higher rates of job loss. Objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…The data were collected between 14 April and 9 May 2021 when the third national state of alarm ended in Spain leading to easing of the movement restrictions. The response rate to the survey used in this study was 93.6% which is comparable to that of other previous studies carried out in similar patient groups [ 27 , 28 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The data were collected between 14 April and 9 May 2021 when the third national state of alarm ended in Spain leading to easing of the movement restrictions. The response rate to the survey used in this study was 93.6% which is comparable to that of other previous studies carried out in similar patient groups [ 27 , 28 ].…”
Section: Discussionsupporting
confidence: 85%
“…This result is especially alarming if we also consider that obesity or being overweight are risk factors for the development of cardiovascular diseases, which represent one of the main causes of premature death in patients with schizophrenia [ 27 , 31 , 33 ]. In line with this data, the results of a recent study carried out during the pandemic in patients with mental disorders found a higher body mass index compared to the general population.…”
Section: Discussionmentioning
confidence: 99%
“…The severity of positive and negative symptoms was assessed by using the positive and negative syndrome scale (PANSS). 21,22 The Cronbach's alpha of PANSS in this study was 0.94.…”
Section: Data Collection Instrumentsmentioning
confidence: 47%
“…Furthermore, academic disadvantage and unemployment in schizophrenia are all part of a vicious cycle that frequently results in poor academic performance and joblessness. 21 , 30 , 31 …”
Section: Discussionmentioning
confidence: 99%
“…The results of this study also show that PWS who are employed are less likely to experience depression than those who are not. Previous studies have well documented that employment provides productive benefits to patients and improves individual health and lifestyle quality [66,67].…”
Section: Discussionmentioning
confidence: 99%